Contextual Ecclesiology through Cultural Images: Spiritual and Devotional Models of the Church in Java - Tedjoworo, Hadrianus (Journal of Contemporary Rituals and Traditions, 2025)
Purpose: This study explores the construction of contextual models of the Catholic Church in Java by correlating cultural, biblical, and theological images. It addresses a gap in ecclesiological studies where local cultural symbols—such as pamong, ziarah, and padepokan—have not been systematically incorporated into Church models, despite their strong presence in the lived faith experiences of Javanese Catholics. Methodology: The research employs a qualitative approach using a reflective-hermeneutic method. It is based on secondary sources, including theological literature, cultural studies, and pastoral reflections. Thematic and narrative analysis is used to develop ecclesiological models grounded in symbolic and imaginative representations of the Church within the Javanese cultural context. Findings: The study formulates three contextual models of the Church: (1) the cultural model, emphasizing community participation and cultural rootedness; (2) the spiritual model, reflecting a contemplative and wisdom-oriented ecclesiology; and (3) the devotional model, centered on sacramental and prayerful expressions of faith. These models reveal that Javanese Catholics experience and shape their ecclesial identity through local symbols and religious imagination rather than abstract doctrines. Implications: The findings offer a practical theological framework for enhancing catechesis, pastoral leadership, and ecclesial policy through inculturated practices. The models also serve as references for other culturally diverse Church communities, particularly in Asia and Africa, seeking to integrate faith with local spiritual traditions. Originality and Value: This study introduces the imagerial method, an original theological approach that prioritizes imagination and symbolic experience in ecclesial construction. It contributes a systematic, bottom-up ecclesiology rooted in lived cultural expressions, offering an innovative response to the limitations of dogmatic and top-down Church models.